Patient-reported outcomes of parenteral somatostatin analogue injections in 195 patients with acromegaly. Issue 3 (March 2016) - Strasburger, Christian J; Karavitaki, Niki; Störmann, Sylvère; Trainer, Peter J; Kreitschmann-Andermahr, Ilonka; Droste, Michael; Korbonits, Márta; Feldmann, Berit; Zopf, Kathrin; Sanderson, Violet Fazal; Schwicker, David; Gelbaum, Dana; et al.
Abstract : Background: Long-acting somatostatin analogues delivered parenterally are the most widely used medical treatment in acromegaly. This patient-reported outcomes survey was designed to assess the impact of chronic injections on subjects with acromegaly. Methods: The survey was conducted in nine pituitary centres in Germany, UK and The Netherlands. The questionnaire was developed by endocrinologists and covered aspects of acromegaly symptoms, injection-related manifestations, emotional and daily life impact, treatment satisfaction and unmet medical needs. Results: In total, 195 patients participated, of which 112 (57%) were on octreotide (Sandostatin LAR) and 83 (43%) on lanreotide (Somatuline Depot). The majority (>70%) of patients reported acromegaly symptoms despite treatment. A total of 52% of patients reported that their symptoms worsen towards the end of the dosing interval. Administration site pain lasting up to a week following injection was the most frequently reported injection-related symptom (70% of patients). Other injection site reactions included nodules (38%), swelling (28%), bruising (16%), scar tissue (8%) and inflammation (7%). Injection burden was similar between octreotide and lanreotide. Only a minority of patients received injections at home (17%) and 5% were self-injecting. Over a third of patients indicated a feeling of loss of independence due to the injections, and 16% reported repeated work loss days. Despite the physical, emotional and daily life impact of injections, patients were satisfied with their treatment, yet reported that modifications that would offer major improvement over current care would be 'avoiding injections' and 'better symptom control'. Conclusion: Lifelong injections of long-acting somatostatin analogues have significant burden on the functioning, well-being and daily lives of patients with acromegaly.